An Analysis of Directive Speech Acts Found in “The Expendable 2” Movie - I Gede krisna Dea putra; Komang Dian puspita Candra (Institut Agama Islam Negeri Palopo, 2024)
This study aims to identify the different types of directive speech acts in The Expendables 2movie, focusing on the main character, Barney Ross. The data were analyzed used theory from Searle and Vandervaken (1985). This study used qualitatively to gather and interpret data from the movie's conversations. The study uses an observation method to collect data. This involves watching the movie and examining the script to identify various types of directive speech acts. The process involves reading and note-taking to analyze these acts, uncovering four types of directive speech acts: commands, requests, advice, and questions. Out of 37 instances identified, there were 32 (86.49%) commands, 2 (5.41%) requests, 2 (5.41%) pieces of advice, and 1 (2.70%) question. The findings show that commands are the most prevalent type of directive speech act in the movie.